Strategi Komunikasi Untuk Meningkatkan Kualitas Pengalaman Akademik Melalui Digitalisasi Layanan: Studi Kasus Sistem Informasi Akademik Bakrie Information Gateway 2.0 Tahun Akademik 2024-2025 - Muhammad Rassya Saputra; Eli Jamilah Mihardja (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
The digital transformation of academic administration services in higher education presents opportunities and challenges for students, lecturers and education staff as stakeholders in the academic field. Bakrie University, through the implementation of the Bakrie Information Gateway 2.0 Academic Information System which functions as a digital information channel in academic administration activities, provides accessibility for stakeholders in accessing information in unlimited space and time. However, the process of digitizing academic services that occurred contained communication barriers experienced by stakeholders in the Bakrie Information Gateway 2.0 Academic Information System due to differences in understanding and interpretation of digital technology. This research aims to explore stakeholders perspectives and social construction of the digitalization of academic services, identify the level of importance of involvement of each stakeholder in the process of digitalizing academic services, and analyze the communication strategies implemented by managers in improving the quality of the academic experience through digitizing services on the Bakrie Information Gateway 2.0 Academic Information System. With a qualitative approach and case study method, this research uses social construction of technology theory, stakeholder salience model, and institutional theory of organizational communication to reveal cases in depth and detail to informants. The research results show that stakeholders perceptions and social constructions do not always contain the same elements regarding the digitalization of academic services and students being the main priority in fulfilling academic needs carried out by administrators. In overcoming communication barriers experienced by stakeholders, managers carry out institutional value-based communication strategies to build stakeholder involvement in the digitalization of academic services. By implementing institutional-based communication strategies, managers can improve the quality of the academic experience that stakeholders have.